Legal Position of Foreign Citizens Regarding Ownership of Land Ownership Rights by Inheritance Based on Notarial Deeds - Kasih, Chintya Cinta; Suwondo, Denny; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This research aims tounderstand and analyze the legal position of foreign citizens regarding the ownership of land ownership rights by inheritance based on a notarial deed, as well as analyze the form of notary responsibility for the transfer of ownership rights to land by inheritance to foreign citizens based on the deed he madeThe research method used is ynormative uridis with analytical descriptive research specifications. DThe data required includes primary data and secondary data using data collection techniquesdocumentation or literature study is then analyzed using qualitative approach.Based on the research results, it shows that kThe legal position of foreign citizens regarding indirect ownership of land with a notarial deed is that a person's civil rights to inheritance cannot be lost except due to actions that are detrimental to the inheritance of the heir (the person who died) as regulated in Article 838, Article 839, 832 and 852 of the Civil Code. The form of notary responsibility for the indirect transfer of land ownership rights to foreign citizens is that the notary, in carrying out his profession in providing services to the public, must act in accordance with applicable laws and regulations and the notary's code of ethics to guarantee the truth of his actions. Keywords: Citizens; Foreign; Heirs; Land; Property; Rights.